The association between TyG index and cardiovascular mortality is modified by antidiabetic or lipid-lowering agent: a prospective cohort study - Changchang Fang; Nanqin Peng; Jiang Cheng; Xiyu Zhang; Wenli Gu; Zicheng Zhu; Xiaoping Yin; Zhiwei Yan; Jing Zhang; Peng Yu; Xiao Liu (Cardiovascular Diabetology)
Abstract Background The triglyceride-glucose (TyG) index is recognized as an alternative measure of insulin resistance (IR) and has been linked to the risks of cardiovascular disease (CVD) and mortality. This study aimed to evaluate whether the association between the TyG index and CVD mortality is influenced by the use of antidiabetic and hypolipidemic agents, given their potential modifying effects on the TyG index. Methods Participants from the National Health and Nutrition Examination Survey (1999–2018) were included in the study. Mortality outcomes were tracked through linkage with National Death Index records until December 31, 2019. Data on the use of antidiabetic and hypolipidemic medications (including prescribed insulin, diabetic pills, and cholesterol-lowering agents) were self-reported by participants. Results A total of 5,046 adults (representing 42,753,806 individuals, weighted mean age 61.08 years [SE: 0.24]; 49.35% female) were analyzed. The TyG index was significantly associated with all-cause and CVD mortality, and these associations were modified by the use of antidiabetic and hypolipidemic agents (p < 0.01). Significant interactions were observed between the TyG index and the use of these agents for mortality outcomes after full adjustments (p-value for interaction < 0.05). Exposure-effect analysis revealed a U-shaped relationship between TyG index levels and the risks of all-cause and CVD mortality in participants using these agents, while a linear positive relationship was observed in participants not using these agents. Conclusions The use of antidiabetic and hypolipidemic agents modify the association between the TyG index and all-cause and CVD mortality. These findings suggest that future studies on the TyG index and its relationship with CVD and mortality should account for the modifying effects of these agents. Graphical abstract